Topical delivery of aceclofenac as nanoemulsion comprising excipients having optimum emulsification capabilities: preparation, characterization and in vivo evaluation. (April 2013) - Dasgupta, Sandipan; Dey, Sanjay; Choudhury, Supratik; Mazumder, Bhaskar
<x xml:space="preserve">Abstract</x> Objective: The aim of the present study was to investigate the potential of a nanoemulsion for topical delivery of aceclofenac using different excipients having optimum emulsifying ability rather than their solubilizing capacity. Methods: The oil-in-water nanoemulsions were prepared by screening the excipients from the nanoemulsion region of pseudoternary phase diagram. The prepared nanoemulsions were subjected to different thermodynamic stability tests. The nanoemulsion formulations that passed thermodynamic stability tests were characterized for viscosity, droplet size, transmission electron microscopy, refractive index and in vitro skin permeation. The in vitro skin permeation profile of optimized nanoemulsion formulation (NE31, containing 23.85% Polyoxy-35-castor oil, 7.95% PEG 400 and 13.6% Triacetin) was compared with that of nanoemulsion gel (NG31) and marketed gel formulation (HIFENAC GEL (HIG)). In vivo anti-inflammatory efficacy studies were also carried out for NE31, NG31 and HIG. Results: The significant (p < 0.001) increase in in vitro permeability and in vivo anti-inflammatory efficacy of the NG31 formulation was observed as compared with HIG formulation. Conclusion: It can be concluded that the selection of surfactant and cosurfactant on the basis of their emulsification capabilities other than the solubilizing capacity of drug is an important criterion for the formulation of nanoemulsion.